Gendered Effects of Employment Protection on Earnings Mobility - Elena Bárcena-Martín; Samuel Medina-Claros; Salvador Pérez-Moreno (Global Labor Organization (GLO), 2020)
This paper explores potential gendered effects of employment protection on earnings mobility, differentiating between upward and downward movements. We conduct a micro-macro mobility analysis for 23 European countries over the economic downturn period 2008–2014. The results confirm that, overall, the higher the protection for regular contracts, the lower the earnings mobility (either upwards or downwards) although the effect is stronger among women of high reproductive age. Nevertheless, protection for temporary employment seems to be only associated with reduced downward earnings mobility when considering transitions into and out of employment, with no gender differential effect.
Keywords: D31; J08; J13; J31; J60; O15; 330; earnings mobility; employment protection; European countries; gender